Effect of Soybean Sprout Concentration on The Nutritional Content of Jelly Candy in Different Processing Temperature - Hayuningtyas, Afwa; Sebayang, Enda Oktavia Br; Rahmi, Suci; Maliza, Noer Octaviana (Journal of Nutrition Science, 2024)
Jelly candy is one of the processed foods that is popular among all ages. Generally, Jelly candy produced on the market contains sugar, water, and essence only, without considering its nutritional content. As it is low nutritional content, it needs a great strategy to produce nutritious jelly candy by replacing the raw material with other ingredients that are rich in nutrients such as soybean sprouts. Soybean sprouts contain high protein (127% higher than soybean seeds), which is an important component for support growth, development, and maintenance of the human body tissues. This study provides food diversification in jelly candy that is rich in protein, by analyzing the effect of concentration of soybean sprout juice (0%, 40%, 70%, and 100%) and processing temperature (high temperature using oven (80ᵒC) and low temperature using refrigerator (5ᵒC)) using a 4x2 factorial randomized design. The results showed that there was no significant effect (P<0.05) between treatments in the analysis of moisture, protein and carbohydrate content, but there was no significant difference (P><0.05) of soybean sprout concentration and processing temperature between treatments in the parameters of moisture and ash content, but a significant difference (P<0.05) between treatments in the analysis of moisture, protein and carbohydrate content, but there was no significant difference (P><0.05) showed in the parameter of fat, protein, and carbohydrate content. The best treatment was obtained by adding 100% soybean sprouts and processed in the refrigerator (low temperature), with an average of 18.43% moisture content, 0.82% ash content, 7.75% fat content, 9.75% protein content, and 37.09% carbohydrates.